2018
DOI: 10.3389/fphar.2018.01330
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Primary Epithelial Cell Screening Tool to Investigate Phage Therapy in Cystic Fibrosis

Abstract: Antimicrobial-resistant microbes are an increasing threat to human health. In cystic fibrosis (CF), airway infections with Pseudomonas aeruginosa remain a key driver of lung damage. With few new antibiotics on the development horizon, alternative therapeutic approaches are needed against antimicrobial-resistant pathogens. Phage therapy, or the use of viruses that infect bacteria, is one proposed novel therapy to treat bacterial infections. However, the airways are complex microenvironments with unique characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…Therefore, the objective of this study was to determine whether a synergistic effect exists between the virulent phage E79 and the antibiotic aztreonam lysine (AzLys) [ 20 ] on P. aeruginosa strain PA01 in vitro. Trend et al [ 21 ] showed that phage E79 does not induce apoptosis or the production of inflammatory cytokines on airway epithelial cells isolated from children with or without CF. They also consider the potential of E79 as a phage therapy agent due to its wide host range against P. aeruginosa clinical isolates, stable high-titer stocks, and no known presence in bacterial pathogenicity islands [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the objective of this study was to determine whether a synergistic effect exists between the virulent phage E79 and the antibiotic aztreonam lysine (AzLys) [ 20 ] on P. aeruginosa strain PA01 in vitro. Trend et al [ 21 ] showed that phage E79 does not induce apoptosis or the production of inflammatory cytokines on airway epithelial cells isolated from children with or without CF. They also consider the potential of E79 as a phage therapy agent due to its wide host range against P. aeruginosa clinical isolates, stable high-titer stocks, and no known presence in bacterial pathogenicity islands [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trend et al [ 21 ] showed that phage E79 does not induce apoptosis or the production of inflammatory cytokines on airway epithelial cells isolated from children with or without CF. They also consider the potential of E79 as a phage therapy agent due to its wide host range against P. aeruginosa clinical isolates, stable high-titer stocks, and no known presence in bacterial pathogenicity islands [ 21 ]. Our results extend these previous findings and identify a PAS effect of increased time to lysis, increased infection efficiency and plaque sizes by E79 in the presence of AzLys, as well as the increased destruction of biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Preincubation with T4 phage also showed protective activity [ 35 ]. It is known that SARS-CoV and SARS-CoV-2 induce apoptosis and result in lymphocytopenia [ 36 , 37 ]; however, when airway epithelial cells from the human bronchi harvested and cultured phages in vitro, it resulted in reduced apoptosis [ 38 ].…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…We demonstrated protective activity of the T4 phage on the survival of human lung epithelial cells infected with human Adv when the phage was added before or during the entire time of Adv infection; preincubation with the phage was also protective [ 10 ]. Interestingly, while SARS-CoV and SARS-CoV-2 are known to induce apoptosis and resulting lymphocytopenia is a common laboratory finding (>60 of patients and >80% in the dead patients) [ 11 , 12 ], apoptosis is reduced in airway epithelial cells harvested from the human bronchi and cultured with phages in vitro [ 13 ]. Furthermore, both T4 and A3/R (staphylococcal phage) preparations significantly reduce the percentage of DEC-205+ human myeloid cells (lectin receptor recognizing ligands expressed during apoptosis and necrosis of different cell populations) [ 14 ].…”
Section: Phages May Penetrate Epithelial Cells Protect Those Epithelmentioning
confidence: 99%